Control of microstructure architectureof polycaprolactone electrospunscaffolds - Rajendran, R.; Ham, W. J.; Low, C. Y.; Alexander, C. H. C.; Koh, C. T. (2024)
Tissue engineering is an area in which new tissues or organs arereplicated in a promising way to replace damaged tissues ororgans caused by accidents and medical conditions. For cells togrow, a proper environment provided by scaffolds can imitate thecomposition of that original human extra cellular matrix (ECM).This study focuses on the preparation of Polycaprolactone (PCL)nanofibers using electrospinning approach. The effect of processparameters such as PCL concentration, flow rate and voltagesupply on the architecture of microstructure was also studied.The diameter and porosity of the nanofibers were analyzed fromimages taken by Scanning Electron Microscopy. Beads werefound in the electrospun scaffolds due to high humidity. Thebeads formation was reduced by adding PBS salt solution andincreasing the distance of the collector plate from the needle tip.Further, electrospun nanofibers with larger diameters were byhaving higher PCL concentration, higher flow rate and lowervoltage. This study suggests the importance of the control ofhumidity and process parameters during process electrospinningin the control of the microstructure of the electrospun scaffolds